The Darwin wasp Camera thoracica (Szépligeti, 1916) (Ichneumonidae) as a natural enemy of the dreaded Brazilian wandering spider Phoneutria nigriventer (Keyserling, 1891) (Ctenidae) - Pádua, Diego G.; Silva-Santos, Isamara; Santos, Bernardo F.; Faustino-Magalhães, Mayara D.; Souza, Maria N. A.; Kloss, Thiago G. (Zootaxa, 2024)
Wandering spiders (genus Phoneutria) hold a prominent position as some of the world’s most medically significant venomous arachnids, especially in Brazil. In this study, we record and illustrate for the first time, the Darwin wasp Camera thoracica (Szépligeti, 1916) as a natural enemy of the ctenid Phoneutria nigriventer (Keyserling, 1891). Furthermore, we provide a description of the previously unknown male wasp, update and standardize the description of the female, and provide biological notes.